(untitled) (Jurnal Elektronika dan Telekomunikasi, 2022)
High data rates, low latency, and low energy consumption are required for the fifth-generation (5G) mobile wireless network. One of the devices that garner interest to be developed is the antenna. Microstrip antennas are widely used in cellular communications because of their simple profile and easy fabrication. However, it has limitations in terms of performance. The millimeter-wave band has been selected to provide high-speed service in 5G wireless networks. Compared to other frequency bands, the propagation path in millimeter-wave is significantly decreased. The substrate integrated waveguide (SIW) technology aims to integrate all components on the same substrate, with low insertion loss and a low profile. Using a dielectric substrate on top and a metallic coating at the bottom with metalized holes, the SIW structure offers a compact form factor for integrating active circuits, passive components, and radiation elements within the same substrate. Therefore, this study aims to design and implement a reflector integrated microstrip antenna with a compact form and a working frequency of 26 GHz. The measurements showed the return loss value of -11 dB, voltage standing wave ratio (VSWR) of 1.9, and the antenna impedance of 63 Ω. The antenna that was designed and fabricated in this work is suitable for operation in the millimeter-wave range for 5G technology.